CERIF – Is the standard helping to improve CRIS? - Pinto, Carlos Sousa (2014)
Governments and organizations are creating Current Research Information Systems (CRIS) to follow the growth of the amount of research data, providing tools to collect, preserve and disseminate that data. At the same time, we are facing the appearance of standards designed to regulate CRIS development. Common European Research Information Format (CERIF) is a standard for managing and exchanging research data. There are several types of CRIS – institutional, regional, national and international. In this work we have just considered the national and international types of CRIS worldwide. Only seven of them were CERIF compliant. The aim of this study is to conclude if the use of CERIF is increasing the number of features in CRIS and how deep CERIF-compliant CRIS are adopting CERIF. Applying all the criteria considered in our methodology, only ten CRIS were analyzed, four of which are CERIF-compliant. CERIF tends to increase similarities between CRIS, in terms of its features and its data models. However, the need for customization of such systems leads to various implementations of the standard, creating an opposite effect of the one referred before. CRIS non CERIF compliant have as central focus the researchers. The CERIF takes CRIS to focus also on projects and institutions of the research domain. With this exception, the CERIF doesn’t show an increase of the number of features. We also consider the use of Dublin Core to increase interoperability between CRIS.